MANAJEMEN SABAR DALAM SURAH YUSUF (STUDI TAFSIR TEMATIK BERDASARKAN ANALISIS TEKS DAN KONTEKS SERTA KONTEKSTUALISASINYA DALAM KEHIDUPAN KONTEMPORER) - Andi Irawan; Uswatun Hasanah; Lukman Nul Hakim (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2021)
Understanding the Qur'an in context is more important, than in text, in this study will use the approach conveyed by Fazlul Rahman from the Double Movement theory, then the context analysis is added with the analytical method by Abdullah Saeed and this research wants to reveal how the relationship of the story of the Prophet Yusuf as. with the historical life of the prophet Muhammad's da'wah. Contextualization of the meaning of the text of Surah Yusuf and the meaning of the context that surrounds or lies behind the history of the da'wah of the Prophet Muhammad. At that time, Patient Management which became the big theme in this discussion was a conclusion drawn from the meaning of the text and the meaning of the context, so that patient management could be understood as a method to build or manage patience based on the story of the Prophet Yusuf (as) who was able to strengthen the soul of the Prophet Muhammad. peace be upon him in the year of sorrow. In the Qur'an Surah Yusuf verses 102-103 Allah swt explains: “(102) Remember some of the unseen news that We have revealed to you (Muhammad saw.); even though you were not beside them, when they agreed to arrange a ruse (to put the Prophet Yusuf (as.) into the well). (103) and most people will not believe even if you want to. (104) and you do not ask them anything in return (for this call of yours), because that call is a teaching for the whole world.